2009
DOI: 10.1086/605412
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Infection in Women: Increased Transcription of HIV Type 1 in Ectocervical Tissue Explants

Abstract: This is, to our knowledge, the first study to compare ectocervix and endometrium in a tissue explant model of HIV-1 infection and to demonstrate greater HIV-1 transcription in the ectocervix. Our results suggest that the ectocervix is more conducive to HIV-1 replication than is the endometrium and that IL-6 enhances HIV-1 transcription at this site. Thus, the ectocervix is an important site to be considered in heterosexual transmission of HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…In our previous study, we determined that the ECX has the highest level of CD45 expression in the female reproductive tract, indicating an enrichment of leukocytes at this site. 32 Moreover, we have found that the expression of CD4, CCR5, and CXCR4 varied in the ECX and in the EM on both the stromal leukocyte population as well as on epithelial cells, and the numbers and distribution of receptor-positive leukocytes also varied throughout the menstrual cycle, indicating hormonal regulation of receptor expression and leukocyte trafficking. 41,42 Thus, the varied findings among tissue sites is likely due to multiple effects including the density of receptor-positive cells, or to donor variation in age, menstrual cycle stage and/or clinical conditions.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In our previous study, we determined that the ECX has the highest level of CD45 expression in the female reproductive tract, indicating an enrichment of leukocytes at this site. 32 Moreover, we have found that the expression of CD4, CCR5, and CXCR4 varied in the ECX and in the EM on both the stromal leukocyte population as well as on epithelial cells, and the numbers and distribution of receptor-positive leukocytes also varied throughout the menstrual cycle, indicating hormonal regulation of receptor expression and leukocyte trafficking. 41,42 Thus, the varied findings among tissue sites is likely due to multiple effects including the density of receptor-positive cells, or to donor variation in age, menstrual cycle stage and/or clinical conditions.…”
Section: Discussionmentioning
confidence: 82%
“…We previously demonstrated that tissue explants prepared from the female reproductive tract of seronegative women could be infected with HIV-1, and that the level of infection among female reproductive tract sites correlated with expression of the pan-leukocyte marker, CD45. 32 In this study we exposed female reproductive tract explants to siRNA to silence CD4 and CCR5 for 48 h prior to the addition of HIV-1 to determine the efficacy of gene silencing to protect tissue explants from HIV-1 infection. We then measured the degree of gene silencing and of inhibition of HIV-1 reverse transcription on subsequent days of culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of ectocervical tissue from HIV positive women found higher levels of IL-6 than in uninfected controls. Because the ectocervix was an area where high levels of HIV replication had been detected, recombinant IL-6 was applied to tissue explants and a greater than 300-fold increase in HIV transcription was seen (Asin et al, 2009). HIV appears to be capable of not only infecting immune cells, but of using immune response to its own advantage to enhance its replication.…”
Section: Inflammatory Responsementioning
confidence: 99%